If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -3b + 6b = 0 Combine like terms: -3b + 6b = 3b 9 + 3b = 0 Solving 9 + 3b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3b = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 3b = 0 + -9 3b = 0 + -9 Combine like terms: 0 + -9 = -9 3b = -9 Divide each side by '3'. b = -3 Simplifying b = -3
| (X-4)=-8 | | 11p+7p+4p=27 | | Cscx-secx=0 | | 4x^2=20x-28 | | Y=3x(2x-1)(x+3) | | .10(x+7)=30 | | 18=2g | | .25v-.42=.28v-.25 | | -4(x-3)-13=3(x+2) | | V=(10-2x)(8-2x) | | c(3)=15 | | 2x^2=13x+24 | | 6+2x=-6x-90 | | 5x-10+1x+3=8 | | 13+5r=2(5+2r) | | 4(7x+4)-9=28x+7 | | x^3+5x+3x+15=0 | | 4a+2=3a+7 | | 0=-4x^2-16x+20 | | 201(6+6)= | | 2-4h=6-6h | | -50+1.0x=300 | | 4x-3=-103-6x | | Y=-4x-16x+20 | | 2x+5-8w=7-4w | | 3m+3-m=3(m+1) | | -1v+5+4v=1+5v+3 | | (2i+3)(7i+6)= | | 9x+6(3x-4)=12-9x | | 3a-11=4(a+1)+13a+3 | | 2g-8+3g=7 | | .17(x+29)=86 |